Delivering construction education programs through the distance mode: Case study in Australia - Wu, Peng; Pienaar, J.; O'Brien, D.; Feng, Y. (2013)
Distance learning has gone through rapid expansion over the years. Statistics have shown that online enrollment has accounted for 25.3% of total enrollment in degree-granting postsecondary institutions in the United States by the end of 2008. Much has been discussed about the factors contributing to the success of distance courses. However, the design and delivery of distance learning construction programs (DLCPs) should not be overlooked, considering the characteristics of the construction industry and the construction discipline. Central Queensland University (alternatively known as CQ University) has offered DLCPs exclusively by the distance mode since 1990. From more than 20 years of experience, the university has identified a list of factors that can affect the success of DLCPs, including curriculum design, interface design, interactive delivery, and learning communities. It seems that these factors can adequately support the development of DLCPs by bridging the transition process, enhancing the interaction, and increasing disciplinary organized activities, which will then lead to the cognitive development of distance students. The results provide a good guidance of the design and delivery of DLCPs and will be useful for other institutions seeking to implement the distance mode in construction education. © 2013 American Society of Civil Engineers.